Applications of Novel Transformation for Solving Ordinary Differential Equations with Unknown Initial Conditions - Hakim ALshemary, Wasan; Neamah Kadhim, Hayder; Neamah AL Bukhuttar, Athraa (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, we apply the Novel transform to obtain the formulas of general solutions of ordinary differential equations with unknown initial conditions through utilizing the relationship between Novel and Laplace transforms.